Scutellarin Loaded on Ultradeformable Nanoliposome Scutellarin EDTMP (S-UNL-E) Promotes Osteogenesis in Osteoporotic Rats - Teng, Minhua; Yuan, Xiao; Wang, Dashan; Gao, Hui; Zhang, Kaiyue; Wang, Wenxue; Zhao, Baodong (Stem cells international, 2022)
Scutellarin is known as a safe, effective, and low-cost traditional Chinese medicine and has a variety of biological activities. Studies reported that the scutellarin loaded on ultradeformable nanoliposome scutellarin EDTMP (S-UNL-E) could promote osteoblast differentiation and bone formation in vitro. However, its effect on promoting osteogenesis in vivo is still unclear. In this study, pharmacology network and transcriptome sequencing were used to screen the potential targets and pathways of scutellarin in treating osteoporosis. The female Sprague-Dawley (SD) rats were operated on with bilateral oophorectomy and femoral defect to establish an osteoporosis model and then treated separately with bone dust, single scutellarin, 40 mg/kg ultradeformable nanoliposome scutellarin (S-UNL), and the optimal concentration of 40 mg/kg S-UNL-E for a total of 56 d to detect the parameters of trabecular bones. And qRT-PCR and western blot were performed to determine the expression of prostaglandin-endoperoxide synthase 2 (PTGS2), alkaline phosphatase (ALP), transcription factor 4 (TCF4), and β-catenin. Results of microscopic computed tomography (Micro-CT) of trabecular bones showed that single scutellarin, S-UNL, and S-UNL-E all promoted the bone formation of osteoporotic rats, in which S-UNL-E manifested the most remarkable therapeutic effect. And it is found that 40 mg/kg of S-UNL-E increased the expression of PTGS2, ALP, TCF4, and β-catenin, which indicated that S-UNL-E stimulated the secretion of ALP in bone defect areas to promote bone healing, and increased PTGS2 expression thereby enhancing the transcription and translation of key gene β-catenin and TCF4 in the Wnt/β-catenin signaling pathway to treat osteoporotic rats.